(untitled) (Research, Society and Development, 2024)
The purpose of this research was to evaluate the effectiveness of the management of the National School Feeding Program in the municipality of Belém, State of Pará, in 2018. The School Feeding Council and the Public Management Control Network in the State of Pará, consisting of several control bodies, carried out cross-sectional research, in a simultaneous action of a single day, in 10 municipal schools, with the application of a structured instrument on a hedonic sensory scale that evaluated three aspects of school feeding: quality, quantity and frequency of distribution, whose data were evaluated by descriptive statistics. The average of the results expressed by students of Elementary School I and II and preschoolers of Pre-Kindergarten revealed that the acceptability of the quality of food in the capital of Pará expressed 36.1% and the acceptance of the quantity of portions distributed to students was 42.3%, values markedly lower than the official index established for the program (85%); the regularity of the offer (89.8%), indicating that the students consider that there are few failures in the frequency of distribution of school meals. The low rates indicate the low effectiveness of the program and the need for periodic evaluations to monitor and urge its proper execution.